Penelitian pengaruh pelarut metil etil keton terhadap daya rekat bahan perekat dari karet nitril - Bambang Supriyono (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The objective of this research was to identify and obtain a right formula of adhesive made from nitril rubber as raw material and metil etil keton as the solvent, while the concentration and temperature employed were varied. The reason of using metil etil keton as the solvent was among others it was able to dissolve nitril rubber as the raw material of adhesive compound, non toxic.material. Easy to be available and volatile. Nitril, rubber was used as raw material because of its high resistance to oil, water, certain organic solvents and high temperature.